Answer:
We conclude that the two ordered pairs (0, 0) and (-2, 2) are the solutions of the equation y = 2x² + 3x.
Step-by-step explanation:
Given the expression
y = 2x² + 3x
Substituting x = 0
y = 2(0)² + 3(0)
y = 0+0
y = 0
Thus, the ordered pair is: (0, 0)
Now, substituting x = -2
y = 2x² + 3x
y = 2(-2)² + 3(-2)
y = 8 - 6
y = 2
Thus, the ordered pair is: (-2, 2)
Therefore, we conclude that the two ordered pairs (0, 0) and (-2, 2) are the solutions of the equation y = 2x² + 3x.
Answer:
![360 \div 30 = 12](https://tex.z-dn.net/?f=360%20%5Cdiv%2030%20%3D%2012)
Step-by-step explanation:
so Kennedy is right
9514 1404 393
Answer:
(b) One figure is a rotation image of the other
Step-by-step explanation:
The axis of symmetry is horizontal for the left figure, and vertical for the right figure. The right figure has been rotated 90° CW from the left figure.
Answer:
a rhombus
Step-by-step explanation:
If you graph the problem, you can see the shape of the quadrilateral. I attached a picture of a graph below. I hope this helped you!! Have a great rest of your day.
switting upwards this should help